Nutritional experiences of Turkish university students with type 1 diabetes: a qualitative study - Şebnem Özgen Özkaya; Volkan Özkaya; Erman Gedıklı; Muazzez Garıpağaoğlu (Journal of Health, Population and Nutrition)
Abstract Background This study was performed in order to describe the nutritional experiences of university students with Type 1 diabetes who try to carry on their educational and social lives together in diabetes self-management. Methods In this descriptive and qualitative study, face-to-face and semi-structured in-depth interviews were performed with 15 university students with Type 1 diabetes, aged 18–30, resided in Istanbul, who were diagnosed with Type 1 diabetes at least 5 years ago. The data collection process was performed by the researchers. The interviews were recorded and transcribed. The data collected in accordance with the phenomenological approach were processed using guided content analysis. Results In the interview with the participants, whose mean age was 21.86 ± 2.03 years and 66.7% of those were female, 6 themes were listed as positive and negative experiences of students in diabetes management in the university environment, general nutritional preferences, nutritional attitudes in non-routine and social environments, regular nutrition and quality of campus life, nutrition during the exercise/sports period, university support and students’ expectations from the environment and explained by their sub-dimensions. Conclusion The change in living conditions with the transition to campus life, the new social environment, individualization and academic responsibilities make diabetes self-management a challenging, complex and supportive process. This study might guide the enhancement of university students’ living conditions with diabetes.